Cell disruption and extraction for microalgae biorefinery: Focus on deep eutectic solvents moving towards aqueous biphasic system - Soliah Temilade Taj-Liad; Revathi Raviadaran; Davannendran Chandran; Man Kee Lam (Results in Engineering)
This paper aims to critically assess the potential of deep eutectic solvents-based aqueous biphasic system (DES-ABS) for simultaneous microalgae cell disruption and extraction of multiple bio-compounds in a single-step process with an emphasis on microalgae biorefinery. This review proposes a novel integrated approach using green chemicals and energy-efficient methods to optimize resource use and minimize waste, aligning with circular bioeconomy principles based on findings from existing studies. Existing studies have demonstrated that the use of DES for microalgae pretreatment in bio-compound extraction was influenced by water content and polarity which affected extraction yields of up to 80%. Critically, despite existing studies highlighted the versatility of DES to extract both polar and non-polar bio-compounds individually or sequentially through effective selectivity with high extraction efficiencies of up to 90%, limited study has been directed towards an integrated approach of bioprocessing pathway. Furthermore, although cell disruption and extraction have been identified as critical steps in lifecycle of microalgae biorefinery, existing studies have predominantly treated them as separate processes. Hence, future studies should investigate the potential to integrate cell disruption and extraction in a single process using tailored DES-ABS for selective extraction of multiple bio-compound from microalgae. Potential for synergistic effects particularly with ultrasound assistance should be explored to reduce costs, enhance yields and enable scalability. Separation of extracted bio-compounds and recovery of DES should be emphasized to ensure process feasibility and sustainability. Future research should assess environmental and economic viability of DES-ABS for industrial-scale microalgae biorefinery via life cycle and techno economic analysis.